A gamification model for resource sharing in malaysian schools using cloud computing platform - Mohd Nordin, Abdul Rahman; Mohd Fadzil, Abdul Kadir; Syarilla Iryani, Ahmad Saany; Syadiah Nor, Wan Shamsuddin; Abdullahi Nababa, Saidu (2017)
Cloud computing is a technology that delivers a pool of configurable computing resources to the users. The insufficient systems for sharing of resources, poor extended pattern of resource sharing system, inadequate network and computing facilities have become an issue in school management. This article discusses a model for resource sharing in Malaysian schools using cloud computing platform. The sharing of resources is modelled based on Multi-Person Prisoner’s Dilemma and Peer-Approved incentive mechanism that gives justification to users in the resource utilization. The concept of software as a service is adopted to make the model can be managed in the cloud environment. Based on the proposed model, a prototype is developed and deployed into cloud using OpenStack architecture. The prototype is evaluated using questionnaire instrument that is based on four attributes of usability metrics. The result shows that the model usability achieved 79.28% of effectiveness, 81.35% of efficiency, 91.8% of learnability and 93.18% of satisfaction. The proposed model could save the cost of buying computing and storage infrastructure since all the resources are cloud based.